O Brasil pelo mundo: a forma melodramática de Avenida Brasil - Basso, Maressa de Carvalho (2018)
The soap opera Avenida Brasil, shown by Rede Globo in 2012, is considered a milestone in the history of soaps operas in Brazil. In addition to bringing the C class as its main theme, in particular due to populist government policies, this importance was due to the fact that it is, up to the present moment, the fictional narrative from the country exported to more nations and also to bring in its narrative and aesthetic aspects that classify it as a pioneer. This research aims to show what these aspects were and how they were presented and identified by the public. For this purpose, historical moments were used, as well as concepts relevant to this identification.